2002
DOI: 10.1007/bf03327351
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of health-related quality of life to health care utilization and mortality among older adults

Abstract: These results signify that all four dimensions of HRQOL represented by the BRFSS Core HRQOL Module are important predictors of both short-term and long-term adverse health events among older adults. This brief scale may be particularly useful for assessing the health of older adults in clinical settings and large-scale epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(171 citation statements)
references
References 35 publications
9
158
0
4
Order By: Relevance
“…(i.e., activity limitation). These four indicators of health-related quality of life have previously been evaluated for population-based public health surveillance [23][24][25][26][27]. Andresen et al [24] reported that the retest reliability of BRFSS health-related quality of life indicators ranged from moderate to excellent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i.e., activity limitation). These four indicators of health-related quality of life have previously been evaluated for population-based public health surveillance [23][24][25][26][27]. Andresen et al [24] reported that the retest reliability of BRFSS health-related quality of life indicators ranged from moderate to excellent.…”
Section: Methodsmentioning
confidence: 99%
“…Andresen et al [24] reported that the retest reliability of BRFSS health-related quality of life indicators ranged from moderate to excellent. BRFSS healthrelated quality of life indicators are moderately to highly valid [23,[25][26][27] and have acceptable construct, criterion, and known-groups validity [25].…”
Section: Methodsmentioning
confidence: 99%
“…Historically, much of the work on SRH has focused on its predictive ability for a range of health outcomes, including social-psychological wellbeing (5-7), morbidity (8 -10), health care utilization (10 -12), and mortality (10,13,14). More recently, interest in understanding the determinants of SRH has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HRQOL is an important tool, particularly among older adults, since traditional health outcomes do not account for the perceived functional limitations that occur later in life (Centers for Disease Control and Prevention, 2015). Moreover, HRQOL is a more powerful predictor of health services use and mortality than many objective measures of health (Dominick et al, 2002;Otero-Rodríguez et al, 2010;Rodríguez-Artalejo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%